Hubungan Malaysia-Indonesia dalam kerjasama ekonomi dari tahun 1957-2003 - Mohamad Akmal Ibrahim (Tanjong Malim, 2021)
Hubungan Malaysia-Indonesia dalam kerjasama ekonomi dari tahun 1957-2003 by Mohamad Akmal Ibrahim